Kajian Terhadap UU Politik dari Perspektif Gender - Nantri, Ayu Putu (Jurnal Studi Jender SRIKANDI, 2012)
From several public election which held in Indonesia, before outherwise after the reformation, the amount of women representation in parliament are still less in number.As a law state, Indonesia follow the same right in law system, this large been released in UUD 1945 (constitution law) beside that Indonesia has ratification the women political right International Convention and Convention of eleminition for all Discrimination for women and established the equality sence of justice in gender.In fit as the state obligation which followed by women conventon, it has been an obligation for Indonesia to accommodate the convention rules above all the policy. And laws have made for that matter, That is why necessary to be analyzed the political law has arange the rules above.